2021
DOI: 10.7554/elife.70899
|View full text |Cite
|
Sign up to set email alerts
|

Mitochondrial phenotypes in purified human immune cell subtypes and cell mixtures

Abstract: Using a high-throughput mitochondrial phenotyping platform to quantify multiple mitochondrial features among molecularly-defined immune cell subtypes, we quantify the natural variation in citrate synthase, mitochondrial DNA copy number (mtDNAcn), and respiratory chain enzymatic activities in human neutrophils, monocytes, B cells, and naïve and memory T lymphocyte subtypes. In mixed peripheral blood mononuclear cells (PBMCs) from the same individuals, we show to what extent mitochondrial measures are confounded… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
50
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 65 publications
(65 citation statements)
references
References 74 publications
3
50
1
Order By: Relevance
“…Differences in sampling time might underlie these different observations, as Liepinsh et al ( 25 ) sampled directly after exercise while we sampled 21 h after exercise. Since PBMC subsets are metabolically different ( 17 , 18 ) and substantial shifts in PBMC subsets have been described after acute exercise ( 27 – 29 ), the increased mitochondrial PBMC function as observed by Liepinsh et al could possibly be related to large differences in analyzed PBMC subsets between the two timepoints, whereas in our study PBMC composition was similar at baseline and after the recent bout of exercise. Second, differences in the metabolic substrates provided to the PBMCs during metabolic analysis might play a role.…”
Section: Discussioncontrasting
confidence: 38%
See 2 more Smart Citations
“…Differences in sampling time might underlie these different observations, as Liepinsh et al ( 25 ) sampled directly after exercise while we sampled 21 h after exercise. Since PBMC subsets are metabolically different ( 17 , 18 ) and substantial shifts in PBMC subsets have been described after acute exercise ( 27 – 29 ), the increased mitochondrial PBMC function as observed by Liepinsh et al could possibly be related to large differences in analyzed PBMC subsets between the two timepoints, whereas in our study PBMC composition was similar at baseline and after the recent bout of exercise. Second, differences in the metabolic substrates provided to the PBMCs during metabolic analysis might play a role.…”
Section: Discussioncontrasting
confidence: 38%
“…The CD3 + T cells are composed of CD4 + and CD8 + T cells, roughly in a 2:1 ratio. Different PBMC subsets do not only provoke different immune responses but they can also display distinct metabolic states ( 16 18 ). Importantly, apart from providing energy substrates and metabolic building blocks for immune cell proliferation and synthesis of macromolecules (e.g., cytokines), metabolic pathways have recently been shown to not only act as a consequence but also as driver of immune cell differentiation ( 16 ), which further increases the relevance of monitoring cellular metabolism as a biomarker for health.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It should also be noted that although some past studies assayed for mtDNAcn from whole blood, they did not adjust for the effect of platelets, white blood cells, and other leukocytes subgroups on mtDNAcn as we do in this study. mtDNAcn estimates differ amongst the various blood cell types (62), and this significantly impacts whole-blood mtDNAcn estimates and should be adjusted for in association models (also see Discussion below). mtDNAcn and personality are both predictors of mortality (25,36,63), thus making our finding of an association between the two even more intriguing.…”
Section: Discussionmentioning
confidence: 99%
“…A recent study of healthy adults demonstrated that mitochondrial phenotypes measured in PBMCs are confounded by variable composition of immune cell subtypes and urged caution in using PBMCs to assess mitochondrial changes within and between individuals (20). However, there are no data about the influence of immune cell subtypes on mitochondrial phenotypes measured in PBMCs from children.…”
Section: Introductionmentioning
confidence: 99%